Yeasts from macroalgae and lichens that inhabit the South Shetland Islands, Antarctica - Fernandes Duarte, Alysson Wagner; Zambrano Passarini, Michel Rodrigo; Delforno, Tiago Palladino; Pellizzari, Franciane Maria; Zecchin Cipro, Caio Vinicius; Montone, Rosalinda Carmela; Petry, Maria Virginia; Putzke, Jair; Rosa, Luiz Henrique; Sette, Lara Duraes [UNESP] (Wiley-Blackwell, 2016)
Antarctic terrestrial ecosystems are largely dominated by lichens, while shallow coastal environments are mainly covered by macroalgae. The aim of this study was to isolate and to evaluate the diversity of yeasts in different species of macroalgae and lichens collected in South Shetland Islands, Antarctica. A total of 405 yeasts were recovered (205 from macroalgae and 200 from lichens). The yeast community from macroalgae was most diversity than the yeast community from lichen. The dominance index was similar for both substrates. A total of 24 taxa from macroalgae and 18 from lichens were identified, and only 5 were common to both substrates. Metschnikowia australis, Mrakia sp., Rhodotorula glacialis and Glaciozyma litorale were the most abundant yeasts in macroalgae and Cryptococcus victoriae, Rhodotorula laryngis, Rhodotorula arctica, Trichosporon sp. 1 and Mrakia sp. were the most abundant in lichens. Based on molecular and phylogenetic analyses, four yeast from macroalgae and six from lichens were considered potential new species. This is the first study to report the yeast communities from the Antarctic macroalgae Himantothallus grandifolius and lichen Ramalina terebrata. Results suggest that Antarctic phyco and lichensphere represent a huge substrate for cold-adapted yeasts and enhanced the knowledge of the microbiota from extreme environments.